Cytokine Profiling in COVID-19 Patients in a Tertiary Hospital in Saudi Arabia; the Pre-Storm Phase - Alabdely Mayyadah; Conca Walter; AlKaff Morad; Alonaizie Aziza; Almohanna Futwan (International Journal of Coronaviruses, 2022)
Background As COVID-19 immunomodulation has been a part of interest for studies, it has been found that severe coronavirus disease 2019 (COVID-19) is associated with hyper-inflammatory response and increased levels of interleukin-6 (IL-6) and interleukin-10 (IL-10). This can progress to cytokine storm syndrome and eventually development of acute respiratory distress syndrome (ARDS). Interleukin-1 receptor antagonist (IL-1RA) is a protein that is a member of the interleukin 1 cytokine family. Monocyte chemoattractant protein 1 (MCP1) is a small cytokine that belongs to the CC chemokine family. Interferon gamma-induced protein 10 (IP-10) is a protein secreted by several cell types in response to Interferon-Gamma (IFN-γ). All of these have roles in the immune response and eventually development of a cytokine storm. Methods Serum levels of IL-1RA, MCP-1 and IP-10 were measured in a cohort of 21 patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on admission to a tertiary care hospital in Riyadh, Saudi Arabia, as well as in an approximately age-sex matched group of 4 uninfected controls. The study population was classified into severe, moderate, mild and controls. Results Serum levels of IL-1RA, MCP-1 and IP-10 were found to be elevated before the clinical deterioration. Conclusion These cytokines may play a role in early detection of disease severity especially in the pre-storm phase. Medications that target cytokines may prevent the development of an overt cytokine storm.
Keywords: COVID-19